KEANEKARAGAMAN JENIS BIVALVIA DI DESA PARITI KABUPATEN KUPANG - Fahik, Mery (Jurnal Biogenerasi, 2025)
Bivalves have a very important ecological role in coastal waters. As benthic organisms, bivalves function in the filtration process, filtering small particles such as phytoplankton from seawater. This process is not only important for the survival of the bivalves themselves, but also affects water quality and the sustainability of the ecosystem as a whole. The method used in this research is a survey method that includes field data collection, this research was conducted in Pariti Village, Kupang Regency. Data collection was carried out to identify the types of bivalves found in the coastal area of Pariti Village. The methods used were linear transects and quadrat sampling. The analysis that will be carried out includes the shannon-wiener diversity index, evenness index, simpson dominance index and margalef species richness index. Based on the results of field surveys conducted in Pariti Village, Kupang Regency, at three different stations, seven bivalve species were found, namely Anadara granosa, Anadara antiquata, Perna viridis, Crassostrea gigas, Meretrix meretri, Tellina timorensis and Pitar tumens. The ecological index shows that the coastal ecosystem of Pariti Village has a moderate level of diversity (H'=1.564) with a relatively even distribution of species (E=0.873). Species richness was also quite good with species richness index values indicating that there were many bivalve species present (R1=0.739), although there were few dominant species. The low dominance index (C=0.192) indicates that the ecosystem is not dominated by a single species, indicating stable ecosystem conditions.